2017
DOI: 10.26480/mjg.02.2017.24.28
|View full text |Cite
|
Sign up to set email alerts
|

Appraisement of the geologic features as a geo heritage in abu roash area cairo-egypt

Abstract: Egypt contains Geologic Heritage that create much opportunity to develop educational and recreational programs as well as tourism projects. Enhancement of Geologic Heritage and awareness of the importance of Geologic Heritage is a great challenge. This paper focuses on a neglected area inside Cairo that is facing a great destruction from the people living there. The Abu-Roash archaeological site is located at 31ᵒ 02′ 42″ E longitude and 30ᵒ 02′ 42″ N latitude. It is one of the most important areas for educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Second, geological research in Egypt has been intense for many decades, and the available information is rigorously systematized. Third, the cultural heritage of Egypt (e.g., pyramids) is well-known, and it is clear how effectively cultural heritage facilitates the promotion and tourism utility of geological heritage (Abdel-Maksoud and Hussien, 2016;Abdel-Maksou and Abdel-Maksoud, 2017). According to Soliman and Abou-Shouk (2016) and Sallam and Ruban (2017) Egypt has several geosites that reflect its geological history.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, geological research in Egypt has been intense for many decades, and the available information is rigorously systematized. Third, the cultural heritage of Egypt (e.g., pyramids) is well-known, and it is clear how effectively cultural heritage facilitates the promotion and tourism utility of geological heritage (Abdel-Maksoud and Hussien, 2016;Abdel-Maksou and Abdel-Maksoud, 2017). According to Soliman and Abou-Shouk (2016) and Sallam and Ruban (2017) Egypt has several geosites that reflect its geological history.…”
Section: Introductionmentioning
confidence: 99%
“…According to Soliman and Abou-Shouk (2016) and Sallam and Ruban (2017) Egypt has several geosites that reflect its geological history. But, unfortunately, some Protectorates are not currently monitored as a geoheritage place or even not recorded as a protected area (Abdel-Maksou and Abdel-Maksoud, 2017). As well, Sallam et al (2018b) reported that the Protectorates in Egypt and the existing tourism programs do not offer geoconservation and geotourism activities.…”
Section: Introductionmentioning
confidence: 99%